Addressing the impact of ethnicity on asthma care. Issue 3 (June 2020) - Tay, Tunn Ren; Pham, Jonathan; Hew, Mark
Abstract : Purpose of review: In asthma, there is an increasing focus on personalizing treatment by targeting treatable traits. Ethnicity has effects on many biological and behavioural traits, and so is an important consideration when personalizing asthma care. This review has particular relevance in light of current patterns of international migration, which are leading to unprecedented levels of ethnic heterogeneity in many geographic regions. Recent findings: This review examines the effect of ethnicity on three key domains – biological traits, behavioural traits and health system behaviour. Ethnicity influences asthma biology by affecting biomarker reference ranges, response to drug therapy and asthma phenotypes. Ethnicity impacts behavioural traits through its effects on psychosocial well being, adherence and asthma self-management. Ethnic minorities are often disadvantaged with regards to healthcare access and healthcare interactions. Summary: Concerted action is needed to address current issues around behavioural traits and healthcare behaviour, which are influenced by ethnicity. More research is required to understand the impact of ethnicity on asthma biology, especially the interplay between genetic and environmental influences on asthma, and the differential response to asthma therapies.